Resting state functional connectivity in primary insomnia, generalized anxiety disorder and controls. (30th July 2017) - Pace-Schott, Edward F.; Zimmerman, Jared P.; Bottary, Ryan M.; Lee, Erik G.; Milad, Mohammed R.; Camprodon, Joan A.
Abstract: Sleep abnormalities are extremely common in anxiety disorders and may contribute to their development and persistence. Their shared pathophysiological mechanisms could thus serve as biomarkers or targets for novel therapeutics. Individuals with Primary Insomnia were age- and sex-matched to controls and to persons with Generalized Anxiety Disorder. All underwent fMRI resting-state scans at 3-T. In Primary Insomnia and controls, sleep was recorded for 2 weeks using diaries and actigraphy. All participants completed state-anxiety and neuroticism inventories. Whole-brain connectivity of 6 fear- and extinction-related seeds were compared between the 3 groups using ANOVA. The only significant between-group main effect was seen for connectivity between the left amygdala seed and a bilateral cluster in the rostral anterior cingulate cortex. The latter is believed to exert top-down control over amygdala activity and their interaction may thus constitute an emotion regulatory circuit. This connectivity was significantly greatest in controls while Primary Insomnia was intermediate between that of controls and Generalized Anxiety Disorder. Across Primary Insomnia and control subjects, mean connectivity decreased with poorer sleep. Across all 3 groups, connectivity decreased with greater neuroticism and pre-scan anxiety. Decreased top-down control of the amygdala may increase risk of developing an anxiety disorder with preexisting Primary Insomnia. Highlights: Resting-state fMRI compared controls, insomniacs and Generalized Anxiety groups. Whole-brain connectivity of 6 fear-related seed regions compared between groups. Using ANOVA & cluster-size thresholds, only L amygdala-rostral ACC differentiated. Amygdala-rACC connectivity significantly greater in controls vs. insomniacs and GAD. Connectivity in insomniacs intermediate between controls and GAD.